Students’ Readiness of Learning English Process During the New Normal at Junior High School - hashikin putri; Herfyna ASTY; M. Khairi IKHSAN (RADINKA JAYA UTAMA PUBLISHER, 2023)
During the pandemic, distance learning was thought to be more effective and efficient. In light of this situation, online learning requires learning readiness because of changes in the way students learn. At SMPN 36 Sarolangun, Jambi, the goal of this study is to find out how students’ readiness of learning English processes during the new normal. In this study, researchers used a qualitative descriptive research method. The participants in this study were eighth-grade students at SMPN 36 Sarolangun Jambi. The purpose of this study was to describe students' readiness for a new normal of learning. The researcher chose the sample by looking for students who studied using blended learning. Purposive sampling was used in this research. The researcher found that the school had delivered subject matter online and offline, therefore, the researcher was interested in doing research at that school, which students still did not understand. In this case, the researcher found a problem in that students could not understand the material clearly when school became normal. Students have not been able to concentrate during the teaching and learning process, but there are still a small number of students who concentrate during the learning process. Readiness to learn can be seen in the reactions of most students because they have not been able to ask the teacher during lessons and have not been able to express ideas to the teacher.